Asymptomatic moyamoya syndrome, atlantoaxial subluxation and basal ganglia calcification in a child with Down syndrome - Kyung Yeon Lee; Kun-Soo Lee; Young Cheol Weon (Korean Pediatric Society, 2013)
Down syndrome, the most common chromosomal abnormality, may be associated with various neurologic complications such as moyamoya syndrome, cervical spinal cord compression due to atlantoaxial subluxation, and basal ganglia damage, as well as epileptic seizures and stroke. Many cases of Down syndrome accompanied by isolated neurologic manifestations have been reported in children; however, Down syndrome with multiple neurologic conditions is rare. Here, we have reported a case of Down syndrome in a 10-year-old girl who presented with asymptomatic moyamoya syndrome, atlantoaxial subluxation with spinal cord compression, and basal ganglia calcification. To the best of our knowledge, this is the first report of Down syndrome, in a child, which was accompanied by these 3 neurologic complications simultaneously. As seen in this case, patients with Down syndrome may have neurologic conditions without any obvious neurologic symptoms; hence, patients with Down syndrome should be carefully examined for the presence of neurologic conditions.